Structure Stability Under Multiparameter Loads - Radoń, U. (Engineering Transactions, 1999)
The precritical response analysis of a structure is generally sufficient for designing purposes. However, the prediction of the response in the postcritical range is essential to identify the ability of the structure to sustain loads at large values of displacements. The modern stability analysis usually consists in generating the equilibrium path for a structure and determining its critical points, but this way is admissible only for one-parameter loads. The formal procedure allows to continue the above procedure for the multiparameter systems, although, equilibrium path should be converted into equilibrium surface or hypersurface. It must clearly be said that this method is useless for the practice due to its complexity. In the paper, the proposal of solving this problem and determining the probability of stability loss is presented.